Pemberdayaan Perajin Umkm Kain Tenun Ikat Dayak Di Desa Ensaid Panjang Kabupaten Sintang Provinsi Kalimantan Barat - Primawan, Ananta; Hamid, Hendrawati (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2023)
This study aims to examine and analyze the process of empowering tie fabric craftsmen in Ensaid Panjang Village, West Kalimantan Province, the inhibiting factors faced and the efforts made to overcome these inhibiting factors. The research method is qualitative, with primary data sources coming from in-depth interviews and observations, as well as secondary data obtained from documentation. Data analysis was carried out using data reduction techniques, data display and drawing conclusions. The research results show that the empowerment of craftsmen is carried out through training activities, counseling, and helping to improve facilities, but this has not yet been running optimally. The inhibiting factor faced by craftsmen is the marketing of ikat products, so there is a need to increase promotional facilitation, both online and offline. Apart from that, there is also the problem of the lack of an empowerment budget, so it is necessary to improve budget management so that assistance can be provided optimally and used according to needs.